2004
DOI: 10.1016/j.orthres.2004.03.017
|View full text |Cite
|
Sign up to set email alerts
|

A novel murine segmental femoral graft model

Abstract: To further understand the cellular and molecular mechanisms underlying cortical bone graft healing, we have developed a novel mouse femur model that permits quantitative and molecular analysis of structural bone graft healing. A 4 mm mid-diaphyseal femoral segment was removed and replaced by either immediate implantation of a fresh autograft, a frozen, genetically identical isograft or a frozen allograft from a different strain of mouse, which was secured with a 22-gauge metal intramedullary pin. Healing was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 47 publications
9
94
0
Order By: Relevance
“…27 At 8 weeks, the dead bone was still not replaced by creeping substitution of new living bone in any of the groups with bone of low osteocyte density. Our results agree with those presented by Tiyapatanaputi et al 28 In a murine segmental femoral graft model, they found that fresh autograft repair occurred by enchondral bone formation at the host-graft junction and by intramembranous bone formation along the length of the graft. Repair of deep frozen grafts (iso-or allograft), however, relied on enchondral bone formation from the host bed, suggesting that live periosteal cells from the host are necessary for repair.…”
Section: Discussionsupporting
confidence: 93%
“…27 At 8 weeks, the dead bone was still not replaced by creeping substitution of new living bone in any of the groups with bone of low osteocyte density. Our results agree with those presented by Tiyapatanaputi et al 28 In a murine segmental femoral graft model, they found that fresh autograft repair occurred by enchondral bone formation at the host-graft junction and by intramembranous bone formation along the length of the graft. Repair of deep frozen grafts (iso-or allograft), however, relied on enchondral bone formation from the host bed, suggesting that live periosteal cells from the host are necessary for repair.…”
Section: Discussionsupporting
confidence: 93%
“…The absence of periosteum also resulted in 75% reduction of osteoclast numbers on bone graft, which correlated with the poor remodeling activity of the devitalized bone allograft or isograft. In contrast, removing cells from the bone marrow had minimal effects on the periosteal bone formation on the donor bone graft [91].…”
Section: Periosteum Is Essential For the Initiation Of Bone Graft Heamentioning
confidence: 87%
“…To gain an understanding of the cellular and molecular mechanisms that define the superior healing of live bone autograft over allograft, we recently developed a murine segmental bone graft model that permits quantitative analyses of structural bone graft healing, remodeling, and graft-host interactions [91]. This model involves the transplantation of a 4-mm mid-diaphyseal femoral bone segment to a host with the same size defect in the femur.…”
Section: Periosteum Is Essential For the Initiation Of Bone Graft Heamentioning
confidence: 99%
“…[40][41][42] Radiological and biomechanical outcome measures in a murine femur model have also been developed and have demonstrated the efficacy of these tissue engineered allografts. 43 …”
Section: Revascularizing Massive Allografts: Prototypic Model Of Tissmentioning
confidence: 99%
“…43 Rosa26 transgenic mice were also incorporated into this model so that live isografts that express bgalactosidase could be transplanted into nontransgenic littermates, and the donor cells could be tracked via X-gal stained histology. 44 These studies clearly demonstrated that superior healing observed in the autografts is attributed to the live periosteal cells that actively participate in the early angiogenic, osteogenic, and osteoclastogenic response.…”
Section: Tissue Engineered Periosteummentioning
confidence: 99%